Arthroscopic Capsular Shrinkage for Treatment of Chronic Lateral Ankle Instability. (October 2017) - Vuurberg, Gwendolyn; de Vries, Jasper S.; Krips, Rover; Blankevoort, Leendert; Fievez, Alex W.F.M.; van Dijk, C. Niek
Background: Capsular shrinkage is an arthroscopic stabilization technique that can be used in patients with chronic ankle instability (CAI), if desired in addition to primary arthroscopic procedures. Despite positive short-term results, long-term follow-up of these patients has not yet been performed. Therefore, our objective was to assess whether capsular shrinkage still provided functional outcome after 12-14 years compared to preoperative scores. Methods: This study was a retrospective long-term follow-up of a prospectively conducted longitudinal multicenter trial. The study duration was from February 2002 to September 2016, including a preoperative assessment and short-, mid-, and long-term follow-up. At the time of inclusion, patients were diagnosed with CAI, >18 years old, were unresponsive to conservative treatment, and had confirmed mechanical ankle joint laxity. Patients were excluded if the talar tilt was greater than 15 degrees, if they had received previous operative treatment, or had constitutional hyperlaxity, systemic diseases, or osteoarthritis grade II or III. The primary outcome was the change in functional outcome as assessed by the Karlsson score. Results: Twenty-five patients of the initial 39 were available for this follow-up. This group had a mean age of 43.2 years (SD±11.1) and included 15 males. A statistically significant improvement was found in the Karlsson score at 12-14 years (76.6 points; SD±25.5) relative to the preoperative status (56.4 points; SD ±13.3; P < .0005). Although 17 patients (68%) reported recurrent sprains, 23 patients (92%) stated that they were satisfied with the procedure. Conclusions: Despite improved functional outcome and good satisfaction in patients with CAI after capsular shrinkage, recurrence rates and residual symptoms were high. For this reason, arthroscopic capsular shrinkage is not recommended as joint stabilization procedure in patients with CAI. Level of Evidence: Level IV, case series